1998
DOI: 10.1093/ajcn/68.4.768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of margarine compared with those of butter on blood lipid profiles related to cardiovascular disease risk factors in normolipemic adults fed controlled diets

Abstract: Effects of butter and 2 types of margarine on blood lipid and lipoprotein concentrations were compared in a controlled diet study with 23 men and 23 women. Table spreads, added to a common basal diet, provided 8.3% of energy as fat. Diets averaged 34.6% of energy as fat and 15.5% as protein. Each diet was fed for 5 wk in a 3 x 3 Latin-square design. One margarine (TFA-M) approximated the average trans monoene content of trans fatty acid-containing margarines in the United States (17% trans fatty acids by dry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 33 publications
5
41
1
3
Order By: Relevance
“…Lp(a) particles (consisting of LDL that includes a glycoprotein called ApoA) are also associated with increased CHD risk. TFA consumption increased Lp(a) levels in six studies (Mensink et al, 1992;Almendingen et al, 1995;Aro et al, 1997;Clevidence et al, 1997;Judd et al, 1998;Lichtenstein et al, 2003) but not significantly in one study (Muller et al, 1998a). A meta-analysis of these trials indicated that TFA significantly raises Lp(a) in comparison to SFA, MUFA, or PUFA (Mozaffarian and Clarke, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lp(a) particles (consisting of LDL that includes a glycoprotein called ApoA) are also associated with increased CHD risk. TFA consumption increased Lp(a) levels in six studies (Mensink et al, 1992;Almendingen et al, 1995;Aro et al, 1997;Clevidence et al, 1997;Judd et al, 1998;Lichtenstein et al, 2003) but not significantly in one study (Muller et al, 1998a). A meta-analysis of these trials indicated that TFA significantly raises Lp(a) in comparison to SFA, MUFA, or PUFA (Mozaffarian and Clarke, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In three trials (Mensink and Katan, 1990;Zock and Katan, 1992;Aro et al 1997), partially hydrogenated high-oleic-acid sunflower oil (not often used in commercially available food products) was the main source of TFA, in which 18:1 nÀ9 (D9) elaidic acid was the most common TFA isomer. Partially hydrogenated soybean oil was used in three other trials (Almendingen et al, 1995;Muller et al, 1998a;Lichtenstein et al, 1999), and in four trials the source of TFA was not specified (Judd et al, 1994(Judd et al, , 1998(Judd et al, , 2002Lovejoy et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…A more recent cross-over trial of regular milk fat, modified (low cholesterol) milk fat and margarine (Jacques et al, 1999) showed that margarine decreased LDL-cholesterol by 12%. Wood et al (1993) showed a 5% differential in LDL-cholesterol between butter and a high trans-PUFA margarine, and in a comparison of butter and margarines with variable trans fatty acid contents, LDLcholesterol decreased by 11, 9 and 5%, respectively, when semi-liquid, soft and stick margarines were incorporated into the diet (Lichtenstein et al, 1999) and by 4.9 and 6.7% when trans and non trans margarines were compared to butter (Judd et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…included 66 dietary interventions ('diets') among men and women involving a total of 518 individuals (Laine et al, 1982;Mensink and Katan, 1990;Zock and Katan, 1992;Judd et al, 1994Judd et al, , 1998Judd et al, , 2002Almendingen et al, 1995;Aro et al, 1997;Muller et al, 1998;Lichtenstein et al, 1999;de Roos et al, 2001;Lovejoy et al, 2002;Sundram et al, 2007). Overall, the mean (s.d.)…”
Section: Effects Of Tfa Replacement: Risk Factorsmentioning
confidence: 99%